Mayflies of the Caucasus Mountains. I. A new species of the genus Electrogena Zurwerra & Tomka, 1985 - Sroka, Pavel; Godunko, Roman J. (Zootaxa, 2012)
Based on the material recently collected in the Western Caucasus Mts., Russian Federation, Electrogena gibedede sp. nov.,new species from the genus Electrogena Zurwerra & Tomka, 1985 is described in detail. The morphological characteris-tics of the adults and larvae of the species are presented (adults of both sexes were reared from the larvae in the field). Thevariability of the species and critical characteristics distinguishing Electrogena gibedede sp. nov. from the remaining rep-resentatives of the genus (focusing mainly on Caucasian species) are described and discussed. In the description of thelarval morphology the standard set of diagnostic characteristics is used. Larval biology and habitat preferences are mentioned. An overview of the present state of knowledge of Electrogena species known from the Caucasus Mts. is provided.